2019
DOI: 10.21825/af.v32i2.15768
|View full text |Cite
|
Sign up to set email alerts
|

Yield Stability and Farmer Preference of Cowpea (Vigna Uncuilata) Lines in semi-arid Eastern Kenya

Abstract: Stability in yields of agronomically acceptable cultivars is generally regarded as the ultimate goal in cowpea improvement. Nine advanced cowpea lines and 3 local checks were evaluated for grain yield in eastern Kenya with the aim of identifying stable genotypes and integrating farmer preferences. The study was conducted in 3 locations over 2 years under a randomized complete block design with 3 replications. Stability was estimated using additive main effects and multiplicative interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The main challenge in intensifying sustainable rice production is the availability of varieties that are resistant to pests and diseases [16]. The genetic resistance of promising lines is expected to solve problems of pests and disease in the field [17,18]. Rice varieties are commonly prone to brown planthopper (Nilaparvata lugens), leaf blast (Pyricularia oryzae), and bacterial leaf blight (Xanthomonas oryzae PV.…”
Section: Introductionmentioning
confidence: 99%
“…The main challenge in intensifying sustainable rice production is the availability of varieties that are resistant to pests and diseases [16]. The genetic resistance of promising lines is expected to solve problems of pests and disease in the field [17,18]. Rice varieties are commonly prone to brown planthopper (Nilaparvata lugens), leaf blast (Pyricularia oryzae), and bacterial leaf blight (Xanthomonas oryzae PV.…”
Section: Introductionmentioning
confidence: 99%
“…This is because AMMI analysis is very efficient in identifying both high yielding and stable genotypes (Asio et al, 2005). AMMI analysis has been extensively used to determine stable cowpea genotypes (Asio et al, 2005;Ddamulira et al, 2015;Horn et al, 2018;Tariku et al, 2018;Kuruma et al, 2019;Abiriga et al, 2020;Haisirikul et al 2020). The AMMI method has also been used to assess the causes of G × E interactions in crops like rye grass (van Eeuwijk and Elgersma, 1993) and wheat (Mohammadi et al, 2017) but not cowpea.…”
Section: Introductionmentioning
confidence: 99%
“…et al (2018),Kuruma et al (2019) andAbiriga et al (2020) who reported only two significant PCAs (PCA1 and PCA2) in their assessment of G × E interactions among cowpea genotypes.…”
mentioning
confidence: 98%